Raising taxes key to accelerate tobacco control in South Asia. (11th April 2017) - Jha, Prabhat; Khan, Javaid; Mishra, Sujata; Gupta, Prakash
Abstract : South Asian countries must prioritise higher tobacco taxation and other control measures to raise the low levels of tobacco cessation and thus avoid millions of premature deaths, say Prabhat Jha and colleagues